Developing Cashless Tourism from a Tourist Perspective: The Role of TAM and AMO Theory - PRAWIRA, Mega Fitriani Adiwarna; SUSANTO, Eko; GOELTOM, Andar Danova Lastaripar; FURQON, Chairul (Journal of Environmental Management and Tourism; Vol 13 No 8 (2022): JEMT, Volume XIII, Issue 8(64), Winter 2022, 2022)
Cashless tourism has become the future of the global tourism industry which is defined as a condition of financial transaction activities for the benefit of tourism that is carried out in a non-cash manner. This condition is motivated by changes in payment technology constantly migrating from conventional to digital models. The creation of increasingly diverse cashless payment channels and internal access has become a catalyst for changes in financial transactions in tourism. This study seeks to uncover factors that influence the internalization of cashless tourism by combining AMO (Abilities, Motivation and Opportunities) and TAM ( Technology Acceptance Model ) Theory. By involving 198 tourists and using the SEM-PLS approach, this study has carefully analyzed that there are 3 (three) phases of cashless tourism internalization: pre-condition, experiences, and internalization. The findings of this study contribute to the understanding of technology adoption in the context of travel and the need to develop digital payments for stakeholders.